THE INFLUENCE OF TALENT MANAGEMENT, MOTIVATION, AND ENGAGEMENT ON EMPLOYEE PRODUCTIVITY AT PT GSI STEEL MELTING PLANT - Susanto, Eddy; Suarmanayasa , I Nengah; Suwena , Kadek Rai (International Journal of Cultural and Social Science, 2025)
Employee productivity is a key factor in organizational success in labour-intensive industries, such as steel smelters. PT GSI faces the challenge of low productivity, as reflected in increased employee absenteeism and job dissatisfaction, despite implementing various management policies. Therefore, this study aims to analyze the effects of talent management, motivation, and Employee Engagement on employee productivity and to test the mediating roles of motivation and engagement. This study employs a quantitative approach with a survey design, selecting a random sample of 153 permanent employees from PT GSI. Data collection was conducted through a questionnaire, whose validity and reliability were assessed using Cronbach's Alpha method and Confirmatory Factor Analysis (CFA). Furthermore, data analysis was conducted using Partial Least Squares (PLS) and Structural Equation Modelling (SEM)  techniques, with a significance level of p < 0.05. The results showed that talent management had a significant effect on employee motivation ( ?= 0.689, p < 0.01) and engagement (?= 0.568, p < 0.01). Additionally, motivation and engagement have been proven to have a significant impact on employee productivity. PLS-SEM path analysis reveals motivation and engagement as effective mediating variables in the relationship between talent management and employee productivity. This study provides academic and practical contributions by revealing the mechanism of productivity improvement through talent management. The implication is that PT GSI needs to develop policies that support talent development, increase employee motivation, and encourage engagement to optimize company productivity.